Hate speech detection from social networking posts using CNN and XGBoost - Shahadat, Ashraf Bin; Rony, Md. Mizanur Rahman; Anwar, Md. Adnanul; Joy, Eialid Ahmed (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.